Про континуальні вузли інтерполювання формул типу Ньютона та Ерміта в лінійних топологічних просторах - Макаров, В.Л.; Хлобистов, В.В.; Демків, І.І. (Видавничий дім "Академперіодика" НАН України, 2007)
Interpolation formulas of the Hermite and Newton types on a continual set of knots which depend on continuous scalar parameters are considered. These formulas for nonlinear operators in the linear topological space are constructed and investigated. They provide the correspondence of “input” and “output” continual data as distinct from the previously known interpolation formulas.